Design And Development Of An Ankle Joint Rotator For Lower Limb Prosthesis - Tai, Pei Li (Universiti Sains Malaysia, 2019)
The common drawback in current existing ankle joint rotators are that they are incapable of providing sagittal plane rotations for squatting and kneeling postures. Some are also not universally adaptable which limits the usability of the device. This work aims to design an ankle joint rotator that is capable of providing users the experience to be able to squat and kneel with ease and comfort. The design was created based on four main parameters which are range of motion, size and mass, degree of freedom and external load. The finalized design was then modelled and assembled for further simulation. A static simulation was done using the Solidworks 2019 software to verify the functionality of the design. The new ankle joint rotator was proven to be able of withstanding external force of 3000N with a safety factor of 5.698. The design of the new ankle joint rotator is capable of achieving its objectives by providing the rotational angles for both squatting and kneeling postures. With further improvements, the design can acquire higher flexibility and function based on ISO standards.